2006
DOI: 10.1017/s0022109000002143
|View full text |Cite
|
Sign up to set email alerts
|

Short-Sale Constraints, Differences of Opinion, and Overvaluation

Abstract: Miller (1977) hypothesizes that dispersion of investor opinion in the presence of short-sale constraints leads to stock price overvaluation. However, previous empirical tests of Miller's hypothesis examine the valuation effects of only one of these two necessary conditions. We examine the valuation effects of the interaction between differences of opinion and shortsale constraints. We find robust evidence of significant overvaluation for stocks that are subject to both conditions simultaneously. Stocks are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
294
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(327 citation statements)
references
References 40 publications
26
294
2
3
Order By: Relevance
“…Therefore, IV is negatively related to future returns possibly because it is a proxy for dispersion of opinion. Note that this conjecture is also supported by the cross-sectional evidence: Diether, Molloy, and Scherbina [2002], Ang, Hodrick, Xing, and Zhang [2005], and Boehme, Danielsen, and Sorescu [2006] find that stocks with higher dispersion of opinion or higher price volatility tend to have lower expected returns, especially when interacted with short sale constraints. Guo and Savickas [2005] show that IV and MV forecast stock returns only when combined.…”
mentioning
confidence: 67%
“…Therefore, IV is negatively related to future returns possibly because it is a proxy for dispersion of opinion. Note that this conjecture is also supported by the cross-sectional evidence: Diether, Molloy, and Scherbina [2002], Ang, Hodrick, Xing, and Zhang [2005], and Boehme, Danielsen, and Sorescu [2006] find that stocks with higher dispersion of opinion or higher price volatility tend to have lower expected returns, especially when interacted with short sale constraints. Guo and Savickas [2005] show that IV and MV forecast stock returns only when combined.…”
mentioning
confidence: 67%
“…Forecast dispersion also served as a proxy for the information environment of a firm (Diether et al, 2002;Park, 2005;Boheme et al, 2006). Accordingly, as the information environment of a firm improves, analysts forecast of the firm would converge.…”
Section: Multivariate Regression Analysis -Forecast Dispersion -Full mentioning
confidence: 99%
“…Forecast dispersion is a proxy for differences in opinions about the value of the firm (Diether et al, 2002;Boheme et al, 2006) reports the impact of changes in listing level on the number of analyst following. Forecast dispersion measured as the standard deviation of analyst forecast standardized by the absolute value of the mean analyst forecast.…”
Section: Change Samplementioning
confidence: 99%
“…Gruber (1996), and Wermers (2000) found that institutional investors are informed traders just by observing their trading behavior. Desai, Ramesh, Thiagarajan and Balachandran (2002), Jones and Lamont (2002), Asquith, Pathak and Ritter (2005), Boehme, Danielsen and Sorescu (2006), Diether, Lee andWerner (2009) andBoehmer, Jones andZhang (2008) analyzed the behavior of short seller's trading activities and recognized that the transactions from short sellers were based on informed trading.…”
Section: Introductionmentioning
confidence: 99%